The Effect of Service Quality and Trust on Purchase Intention in E-Commerce - Louis, Hendrik; Abadi, Ferryal; Ruswanti, Endang (ProBisnis : Jurnal Manajemen, 2023)
This study aims to explore the influence of service quality and trust on purchasing intentions in e-commerce in Indonesia, where in the era of digitalization, there are many different options provided by various kinds of e-commerce with different qualities. E-commerce needs to know how much customer purchase intention focuses on service quality and increasing customer trust by paying attention to reputation, quality of information, product delivery, and transaction security. The population in this study had shopped at one of the e-commerce sites (Tokopedia, Shopee, Bukalapak, Lazada) at least the last 6 months. In this study, 228 respondents who had shopped at Indonesian e-commerce were collected and were analyzed with the purposive sampling method using an online questionnaire. This research is a quantitative research with the Structural Equation Model (SEM) method of Lisrel 88. The results of this study show that the variables of information quality and transaction security do not affect trust, yet reputation variables and product delivery affect trust. Trust variables and service quality have positive effects on the purchase intention variable. These findings have managerial implications for maintaining customer trust and improving service quality to improve customer purchase intentions.